Customers’ perception towards ethical advertisements: the mediating role of religiosity from the Malaysian perspective - Haque, A. K. M. Ahasanul; Neha, Aisath; Ahmed, Faruk; Kabir, S. M. (American Scientific Publishers., 2017)
The fact that potentially unethical advertisements are reaching the marketplace suggests that current methods of evaluating advertisements may be insufficient for some of today’s controversial or innovative advertising strategies. Interestingly, customers are constantly prone to advertisements both directly and indirectly. However, the question arises whether these advertisements are perceived to be ethical in the customers’ mind. Many research experts believe such uncertainty could be an indication of a downfall for the advertising industry. It is worthwhile to be aware of the ethical issues facing advertisers in order to reduce the negative perceptions toward advertisements. Data was collected from 200 Malaysian customers and Structural Equation Modeling (SEM) was used to test the research hypothesis. This research focuses on some major Abstract: perceptions for customers in addressing the perception towards ethical advertising. By examining whether the perceived factors such as, religiosity and emotional appeal positively affect ethical perception, and deceptive messages negatively. The study would provide marketers with a clear understanding on the ethical grounds. Therefore, if the accountable people such as advertisers and businesses work cooperatively and think about the consequences, these problems will be diminished in the future. Several propositions for future research have also been identified.